The Effect of Work Motivation, Work Stress and Work Environment on Employee Performance - Cahyo Kuncoroyekti, Priagung Huda; Yuniawan, Ahyar (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The development of well-structured and sustainable human resources is the primary need of an organization, so that a form of human resource management activities emerges where these activities are a forum for employee performance development which is a series of organizational activities that will be directed to attract, develop, and retain an effective workforce. This study aims to determine the influence of work motivation, work stress, and work environment on employee performance (study at Fancy Bakery).  The population used in this study is all production employees in CV. Fancy Bakery which has 124 employees. In this study, a saturated sampling technique is used, namely a sampling technique where all members of the population are used as samples. Then the data collection method through questionnaires and data analysis uses SPSS version 24. The data analysis techniques used in this study include validity test, reliability test, classical assumption test, multiple regression analysis, hypothesis testing using t-test and determination coefficient test (R2). The results of this study show that independent variables, namely Work Motivation (X1), Work Stress (X2) and Work Environment (X3) have a positive and significant effect on Employee Performance (Y). Based on the determination coefficient of 57.3 percent, employee performance can be explained by independent variables in this study, while the remaining 42.7 percent is explained by variables that are not observed in this study.